Synthesis, DNA interaction and anticancer activity of 2-anthryl substituted benzimidazole derivatives - Sontakke, Vyankat A.; Kate, Anup N.; Ghosh, Sougata; More, Piyush; Gonnade, Rajesh G.; Kumbhar, Navanath M.; Kumbhar, Anupa A.; Chopade, Balu Ananda; Shinde, Vaishali S. (New Journal of Chemistry, 2015)
2-Anthryl benzimidazole derivatives (5-7) with hydrogen, carboxyl and benzoyl substituents at the 5th position have been synthesized using a silica supported periodic acid catalyst. The DNA cleavage activity of 5-7 was studied in the presence of light using pBR322 plasmid DNA and was shown to vary with substitution at the 5th position of benzimidazole derivatives. DNA binding studies using ethidium bromide displacement assay demonstrated the non-intercalative binding mode of 5-7. The anticancer activity of these target molecules was tested against MCF-7 and HL-60 cell lines, and they exhibited remarkable activity in the micromolar range. Cellular uptake and morphological changes were confirmed by fluorescence and confocal microscopy. A molecular docking study was carried out to explore the DNA binding mechanism of 5-7.